Оцінювання фінансового ризику корпорацій за системою виведення Мамдані-Заде - Посохов, Ігор Михайлович (Український культурологічний центр, 2013)
У статті розроблено методику оцінювання інтегрального фінансового ризику корпорацій на основі нечіткої системи виведення Мамдані-Заде. Вона є універсальною та може бути застосована в інших сферах (виробничій, комерційній, інвестиційній, інноваційній). Розроблена методика оцінювання інтегрального фінансового ризику корпорацій може використовуватись у прийнятті рішень у процесах функціонування та прогнозування діяльності корпорацій.

Ensuring sustainable development of the national economy is impossible without effective management of domestic corporations, the implementation of risk management systems in corporations, requires reliable assessment of the risks of modern corporations. Financial risks are the most threatening to the successful operation and development corporations, so their score will increase the efficiency of forecasting and risk management corporations. In this paper the technique of integral assessment of the financial risk of corporations based on fuzzy inference system Mamdani-Zadeh. Іt is universal and can be applied in other areas (industrial, commercial, investment, innovation). The developed method of estimating the integral of the financial risk of corporations can be used in decision-making processes of the operation and prediction of corporate activities and allows you to improve as a methodology of modern risk management, and risk management practices of domestic corporations.
Financial risk assessment of corporations in the system output Mamdani-Zade
Keywords: нечіткі множини; інтегральна оцінка ризику; фінансова звітність; fuzzy sets; integrated risk assessment